Ascomicetos assexuais decompositores de serapilheira na Estação Ecológica do Rio Ronuro, Mato Grosso, Brasil - Barbosa, Gleyson Cristiano Korpan (2021)
The Amazon rainforest is one of the largest reservoirs of biodiversity on the planet and its forest formation and edaphoclimatic conditions are conducive to the development of different types of life forms. Among the various forms of life that exist, we can find fungi, which are present in the litter, decomposing organic matter and helping to nourish the Amazonian soils that are naturally poor. It is estimated that there are between 2.2 and 3.8 million species of fungi in the world, however, only 100 to 120 thousand species are cataloged and known by science. Thus, there is still much to be discovered and studies of diversity and taxonomy are the way for this to happen. The work aimed to carry out a taxonomic study of asexual ascomycetes at the Ronuro River Ecological Station. Field expeditions were carried out to ESEC of Rio Ronuro, Nova Ubiratã-MT. Decomposing plant material was collected at 24 points, stored in paper bags and sent to the Microscopy Laboratory of the Biological Collection of the Southern Amazon (ABAM-UFMT). The samples were washed, accommodated in humid chambers and visualized under a stereomicroscope for the collection of reproductive structures of asexual ascomycetes. The specimens were fixed on permanent slides containing PVL resin and visualized under an optical microscope. For identification, microphotographs were obtained and specific literature was consulted. In this work, 64 taxa were found, distributed in 15 orders, 20 families, and 46 genera. Additionally, a new genus and two new species have been described and illustrated, as well as 3 new species records for Brazil. Data on species richness, frequency and occurrences were presented.